Sexual dysfunction among women with breast cancer in northeastern of West Malaysia - Siang, Ooi Poh (2020)
Background: Female sexual dysfunction (FSD) is a common complication among breast cancer patients following their treatment. Aim: The present study assessed the prevalence and the associated factors for female sexual dysfunction among the breast cancer patients in Kelantan. Methods: This is a cross-sectional study recruiting female patients, aged 18 – 65, married and sexually active with the partner, who were diagnosed with breast cancer and had underwent breast surgery, excluding those with underlying psychiatry disorders, previous pelvic surgery and husband with sexual problem. The questionnaire contains demographic, clinical information, together with Malay Version of Breast Impact of Treatment Scale. Their sexual function was evaluated by using Malay Version of Female Sexual Function Index-6. The data was analysed with simple and multiple linear regression. Results: Ninety-four eligible patients were recruited into this study. 73.4% (n = 69) of the patients reported to have sexual dysfunction. Family history of breast cancer (p = 0.040), duration of marriage (p = 0.046) and frequency of sexual intercourse (p = 0.002) are the significant associated factors for female sexual dysfunction in breast cancer patients after surgery. Clinical Implications: More patients should be screened for sexual dysfunction at outpatient department and appropriate counselling can be provided to them if they were positive. Strengths and Limitations: The strength of this study is that this is a local study that using simple version of questionnaire to screen for FSD among the breast cancer patients, also to identify the likely possible factors that leading to it. The limitation includes the causal relationship cannot be established since a cross sectional study design was used. Also, there were few eligible patients who were approached but refused to participate in this study due to embarrassment and sensitive with the topic. Conclusions: 73.4% of patients developed female sexual dysfunction after the treatment for breast cancer and the three significant associated factors that influence the female sexual dysfunction score are family history of breast cancer, duration of marriage and frequency of sexual intercourse.